Los relatos de la pasión como memoria y narración ritual - Zúñiga Valerio, Hanzel J. (2023)
This paper synthesizes literary and theological elements once contained in the canonic gospel’s passages of “the passion of Christ”. The main conclusions that contemporary historiography and exegesis have obtain are introduced through the usage of the narrative genre and the selective reconstruction of memory. These refer to the death of Jesus in order to understand the texts as primitive ritual narratives that respond to the degradation suffered by the ignominious and sudden death of their leader on the cross.